Formation of intermetallic and its effect on the hardening of welding joint between vanadium alloy and Hastelloy X alloy after heat treatment. (March 2023) - Jiang, Shaoning; Shen, Jingjie; Nagasaka, Takuya; Muroga, Takeo; Sagara, Akio; Ohnuki, Somei; Hokamoto, Kazuyuki; Rao, Weifeng; Tanaka, Shigeru; Inao, Daisuke; Morizono, Yasuhiro; Kasada, Ryuta; et al.
Highlights: Solid solution with high-density dislocations appeared at the interlayer after EXW. Ni 3 Ti intermetallic formed at the interlayer of the dissimilar-welding joint after heat treatment above 700 ℃. Ni 3 Ti intermetallic makes a dominant contribution to the hardness. Abstract: Vanadium alloy and Hastelloy X alloy was jointed by explosive welding (EXW), followed by post-weld heat treatment (PWHT). The formation of intermetallic within the welding joint and its effect on hardening were investigated. In terms of morphology, the joint after EXW is characterized by typical waved interface with discontinuous vortex. The cross-sectional samples at the vortex indicate that an interlayer between NH2 and HX formed after EXW and PWHT. The microstructure evolution and corresponding hardness of the interlayer were analyzed. The microstructural observation showed that the interlayer after EXW exists as solid solution with high-density dislocations. The solid solution with a structure of FCC is a mixture of vanadium alloy and Hastelloy X alloy. The hardening is attributed to solid solution and dislocations. After PWHT at 500 °C, the interlayer still exists in the form of solid solution, whose chemical composition is similar with that at the interlayer after EXW. Dislocation density decreases a little, which causes lower hardness compared with that after EXW. After PWHT above 700 °C, Ni3 Ti intermetallics form, whose size increases and density decreases at 900 °C, and make a dominant contribution to the hardness.